Morfometria de Handroanthus ochraceus e Tabebuia aurea e regeneração natural da vegetação lenhosa em cerrado sensu stricto - Reis, Sheila Aline dos (2018)
The present work deals with the morphometry of Handroanthus ochraceus and Tabebuia aurea and natural regeneration of the woody vegetation in cerrado sensu stricto, in the Panga Ecological Reserve, in Uberlândia-MG. The place lives in constant regeneration due to fires and strong invasion by exotic grasses. The morphometry study provides data on tree forms and dynamics, as well as morphometric changes after fire, as well as the importance of some species' forestry. The natural regeneration of plants at sites of major anthropogenic changes exposes the regeneration capacity of species, the most sensitive and resistant species, and which are strong competitors in relation to exotic species. The loss of biodiversity by anthropic actions such as deforestation, burning, agriculture, cattle ranching and etc., shows the importance of the conservation of the Cerrado phytophysiognomies to stay in native species through morphometry and natural regeneration studies. The morphometry of the two species of yellow ipê was made initially through the identification and marking of the trees in the study area, after which the morphometric data were collected, such as total height, crown height, diameter of breast height (DAP) and crown area of each individual. Data were calculated using regression analysis and Principal Component Analysis (PCA). Natural regeneration was done first by demarcating fixed plots (100m2) along equidistant lines throughout the study area, within each plot a smaller plot (4m2) was demarcated, each one equivalent to a plant size class. Larger plots were sampled from 1m to 5cm of DASo, 30 (Class I), smaller plants were sampled from 15cm to 1m high (Class II). The analysis of the regeneration data was done through the total natural regeneration index (RNT), using the density and frequency data of each species, the calculation for the Shannon (H ') and Pielou (J '). The morphometry values of the two study species showed significant differences, H. ochraceus had lower values of total height, DBH and crown area in relation to T. aurea, T. aurea species had larger morphometric characteristics, with tortuous crowns and branches as well as thicker trunks. PCA showed that the degree of slenderness and total height were the components that most explained the data, with 94.29%. 760 individuals belonging to 54 species were sampled. The results of natural regeneration showed that Bauhinia rufa obtained the highest value of RNT (11.79%) and the largest number of individuals (213.0). There was a great difference in the percentage of regeneration between H. ochraceus (RNT: 4.01%) and T. aurea (RNT: 0.42%), showing that T. aurea is slowly regenerating in relation to H. ochraceus. The good biophysical and silvicultural characteristics of both species suggest that the remnant can become an area for the collection of seeds, besides providing silvicultural data for the conservation of the same. The regeneration data showed that the woody vegetation is composed of it has the capacity to regenerate alone, despite the burning and invasion by grasses in the place. However, many species are more sensitive to anthropic disturbances and therefore regenerate more slowly, this characteristic may lead to total exclusion of the species of the remnant, as well as the species T. aurea that obtained good results regarding morphometry, but alarming results and its regeneration, as well as several species sampled, evidencing the importance of the conservation of this area and all vegetation.